COST ANALYSIS OF THERAPY FOR BREAST CANCER PATIENTS WITH HORMONE THERAPY - Vina Purnamasari; Tri Murti Andayani; Achmad Fudholi (Faculty of Pharmacy, Universitas Gadjah Mada)
One of the breast cancer management is done by hormone therapy. This study aimed to determine the main cost component of therapy, the cost of therapy both in outpatient and inpatient, and also the influence of patient characteristics, factor of therapy, and type of hormone therapy on breast cancer treatment costs at RSUP dr Wahidin Sudirohusodo. The research method was an analitic observational study from hospital perspective. The subjects were outpatient and inpatient with breast cancer in the period January-June 2014 at RSUP dr. Wahidin Sudirohusodo who met the inclusion criteria. The data was collected retrospectively which extracted from medical records and the treatment costdata from breast cancer patients. The data was analyzed by calculating the prevalence of breast cancer patients given hormone therapy, major components of costs, and expenses for each component, both for therapy outpatient or inpatient. The results showed that breast cancer patient which included in inclusion criteria were 105 patient. The range cost for inpatient surgerywas Rp 5.436.756 - Rp 5.646.678 with the largest cost component was the medical substance after use (BHP) which included in the cost of medical action 28,6%. The cost range for inpatient chemotheraphy was Rp 2.546.166 - Rp. 6.823.821 with the largest cost component was the cost of drugs namely 83,5%. The cost range for outpatient was Rp 1.538.750 - Rp 4.202.935 with the largest cost component was the cost of drugs namely 63,57%. Patient characteristics that influenced the cost of breast cancer were stage (p = 0,001), medical action (p = 0.001), and cycles of therapy (p = 0,027). In addition, the type of hormone therapy also affects the cost of breast cancer (p = 0,047).Keywords: breast cancer, hormone therapy, cost of therapy